Mutation-Specific Cardiomyocyte Lines from Patients with Fabry Disease: A Sustainable In Vitro Model to Investigate Structure, Function, and Disease Mechanisms - Kathleen Nicholls; Andrea Wise; David Elliot; Menno ter Huurne; Maria Fuller; Sharon Ricardo (International Journal of Translational Medicine)
Background: Fabry disease (FD) results from pathogenic GLA variants, causing lysosomal α-galactosidase A (α-GalA) deficiency and sphingolipid ceramide trihexoside (Gb3 or THC) accumulation. Disease phenotype varies widely but cardiomyopathy is commonly life-limiting. As a multisystemic disorder, FD initiates at the cellular level; however, the mechanism/s underlying Gb3-induced cell dysfunction remains largely unknown. This study established an in vitro mutation-specific model of Fabry cardiomyopathy using human-induced pluripotent stem cell (iPSC)-derived cardiomyocytes to explore underlying cell pathology. Methods: Skin biopsies from consenting Fabry patients and normal control subjects were reprogrammed to iPSCs then differentiated into cardiomyocytes. The GLA mutations in Fabry cell lines were corrected using CRISP-Cas9. Phenotypic characteristics, α-Gal A activity, Gb3 accumulation, functional status, and lipid analysis were assessed. Cardiomyocytes derived from two patients with severe clinical phenotype and genotypes, GLAc.851T>C, GLAc.1193_1196del, and their respective corrected lines, GLAcorr c.851T>C, GLAcorr c.1193_1196del, were selected for further studies. Results: Cardiomyocytes derived from individuals with FD iPSCs exhibited stable expression of cardiomyocyte markers and spontaneous contraction, morphological features of FD, reduced α-Gal A activity, and accumulation of Gb3. Lipidomic profiling revealed differences in the Gb3 isoform profile between the control and FD patient iPSC-derived cardiomyocytes. Contraction strength was unchanged but relaxation after contraction was delayed, mimicking the diastolic dysfunction typical of Fabry cardiomyopathy. Conclusions: iPSC-derived cardiomyocytes provide a useful model to explore aspects of Fabry cardiomyopathy, including disruptions in sphingolipid pathways, proteomics, and multigene expression that together link genotype to phenotype. The platform potentially offers broad applicability across many genetic diseases and offers the prospect of testing and implementation of individualised therapies.